Sex and Risk: Parental Messages and Associated Safety/Risk Behavior of Adult Children. Issue 4 (8th August 2018) - Horan, Sean M.; Morgan, Toni; Burke, Tricia J.
Abstract : The importance of both parent–child conversations about sex and general family communication climates has been emphasized in numerous studies. This study compared general family communication via family communication patterns (FCP) to specific parental communication about sex in understanding young adults' sexual communication/risk (avoidance, threat, and risk behavior). Results suggest that FCP were stronger predictors of adult children's perceptions of sexual communication as threatening and overall avoidance of sexual communication with their partners compared to the frequency of and overall quality of parent–child conversations about sex. Theoretical and practical implications of these findings are also discussed.